2016
DOI: 10.1080/13598139.2016.1264293
|View full text |Cite
|
Sign up to set email alerts
|

Achieving scientific excellence: An exploratory study of the role of emotional and motivational factors

Abstract: This study investigates the perceived role of psychological factors in achieving excellence in scientific research. Six outstanding scientists aged 33-42 were interviewed. Data were analyzed inductively resulting in three main dimensions: personality traits and characteristics, psychological skills and processes, and task-specific strategies. Researchers highlighted the importance of emotional factors and motivational processes to achieve and sustain scientific excellence. Flexible coping, emotion regulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…According to Edwards and Ashkanasy (2018), it is possible to indicate that facts such as academics" research processes take a long time, they have difficulty in balancing work and life, and as a result of this process, they receive rejection responses for publication institutions, poor evaluation of teaching processes, poor feedback and generally insufficient job security are the initiators and enhancers of negative emotions of academicians. Besides, the negative emotions of faculty members can also be explained by the fact that universities generally provide competitive environments (Fischer et al, 2012), by the individual competitive personality traits required for success (Araújo et al, 2017) and by the fact that research topics generally contain stress load.…”
Section: Discussionmentioning
confidence: 99%
“…According to Edwards and Ashkanasy (2018), it is possible to indicate that facts such as academics" research processes take a long time, they have difficulty in balancing work and life, and as a result of this process, they receive rejection responses for publication institutions, poor evaluation of teaching processes, poor feedback and generally insufficient job security are the initiators and enhancers of negative emotions of academicians. Besides, the negative emotions of faculty members can also be explained by the fact that universities generally provide competitive environments (Fischer et al, 2012), by the individual competitive personality traits required for success (Araújo et al, 2017) and by the fact that research topics generally contain stress load.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Araujo, Cruz, and Almeida (2016), six (6) outstanding scientists aged 33-42 were interviewed. The study found out three (3) main dimensions: personality traits and characteristics, psychological skills and processes, and task-specific strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, an increasing amount of social science research has focused on the constructs representing the transformation of an individual’s qualities and effort into high-level outcomes (e.g. Araújo et al., 2017; Young & Reinkensmeyer, 2014). These constructs are referred to with various terms, such as accomplishment, achievement, attainment, eminence, excellence, mastery, performance, proficiency, or success.…”
Section: Introductionmentioning
confidence: 99%